Criminal Act of Sexual Abuse Against Children Based on Law Number 35 Of 2014 and Aceh Qanun Number 6 Year 2014 - Pribadi, Bagus; Zarzani, Riza (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The criminal offense of sexual harassment against children is a serious crime regulated under Law No. 35 of 2014 concerning Child Protection and Aceh Qanun No. 6 of 2014 concerning Jinayat Law. This study aims to analyze the comparison of legal regulations regarding child sexual harassment between the two laws, particularly in terms of definition, criminal sanctions, and protection of children as victims. The Child Protection Law at the national level emphasizes imprisonment and fines, while the Aceh Qanun introduces additional punishments such as whipping and using gold as the basis for fines. This study highlights significant differences between the two regulations, especially in the application of physical punishment and restitution for victims. The research concludes that the application of Sharia law in Aceh provides a distinct approach to protecting children from sexual harassment but does not fundamentally contradict national law.